Growing, evolving and sticking in a flowing environment: understanding IgA interactions with bacteria in the gut. Issue 1 (27th November 2019) - Hoces, Daniel; Arnoldini, Markus; Diard, Médéric; Loverdo, Claude; Slack, Emma
Summary: Immunology research in the last 50 years has made huge progress in understanding the mechanisms of anti‐bacterial defense of deep, normally sterile, tissues such as blood, spleen and peripheral lymph nodes. In the intestine, with its dense commensal microbiota, it seems rare that this knowledge can be simply translated. Here we put forward the idea that perhaps it is not always the theory of immunology that is lacking to explain mucosal immunity, but rather that we have overlooked crucial parts of the mucosal immunological language required for its translation: namely intestinal and bacterial physiology. We will try to explain this in the context of intestinal secretory antibodies (mainly secretory IgA), which have been described to prevent, to alter, to not affect, or to promote colonization of the intestine and gut‐draining lymphoid tissues, and where effector mechanisms have remained elusive. In fact, these apparently contradictory outcomes can be generated by combining the basic premises of bacterial agglutination with an understanding of bacterial growth (i.e. secretory IgA‐driven enchained growth), fluid handling and bacterial competition in the gut lumen. Abstract : We put forward the idea that extensive variations in intestinal and bacterial physiology can explain the apparently contradictory functions of intestinal secretory antibodies (i.e. altering, promoting, or inhibiting colonization of the intestine and gut‐draining lymphoid tissues).